Implementation Of Blended Learning Model Based On Expository Learning And Small Group Discussion In University - Roemintoyo Roemintoyo; Noor Miyono; Mochamad Kamil Budiarto (International Journal of Educational Management and Innovation, 2022)
The purpose of this study is to determine the application of blended learning methods between expository and small group discussion in the Educational Research Course of the Building Engineering Education Study Program. This study follows a quantitative research method with a descriptive approach, with the hope of being able to identify the phenomenon of influence given by the mixed learning model. The sample of this research is 32 students of the Buildin Engineering Education Study Program who take educational research courses. The results of this study also indicate that the integration of the two learning models is proven to provide convenience for students in completing subjects. Almost all students can submit assignments on time for each material is 74%. The application of the combination of the Expository learning model with the Small group discussion method in the course is proven to be able to facilitate students in carrying out assignments according to what is given during learning activities.